Non-Indigenous privilege in health, justice and social services preceding first episode psychosis: A population-based cohort study. (June 2023) - Manuel, Jenni; Cunningham, Ruth; Gibb, Sheree; Petrović-van der Deen, Frederieke S; Porter, Richard J; Pitama, Suzanne; Crowe, Marie; Crengle, Sue; Carr, Gawen; Lacey, Cameron
Background: There is evidence of disparities between non-Indigenous and Indigenous incidence of psychotic disorders. Despite these disparities being a clear signpost of the impact of structural racism, there remains a lack of evidence to target institutional factors. We aimed to investigate non-Indigenous and Indigenous differences in government service use prior to first episode diagnosis as a means of identifying points of intervention to improve institutional responses. Methods: We used a previously established national New Zealand cohort of 2385 13 to 25-year-old youth diagnosed with psychosis between 2009 and 2012 and a linked database of individual-level multiple government agency administration data, to investigate the differences in health, education, employment, child protection and criminal-justice service use between non-Indigenous (60%) and Indigenous youth (40%) in the year preceding first episode diagnosis. Further comparisons were made with the general population. Results: A high rate of health service contact did not differ between non-Indigenous and Indigenous youth (adjusted rate ratio 1.0, 95% confidence interval [0.9, 1.1]). Non-Indigenous youth had higher rates of educational enrolment (adjusted rate ratio 1.2, 95% confidence interval [1.1, 1.3]) and employment (adjusted rate ratio 1.2, 95% confidence interval [1.1, 1.3]) and were 40% less likely to have contact with child protection services (adjusted rate ratio 0.6, 95% confidence interval [0.5, 0.8]) and the criminal-justice system (adjusted rate ratio 0.6, 95% confidence interval [0.5, 0.7]). Both first episode cohorts had a higher risk of criminal justice contact compared to the general population, but the difference was greater for non-Indigenous youth (risk ratio 3.0, 95% confidence interval [2.7, 3.4] vs risk ratio 2.0, 95% confidence interval [1.8, 2.2]), explained by the lower background risk. Interpretation: The results indicate non-Indigenous privilege in multiple sectors prior to first episode diagnosis. Indigenous-based social disparities prior to first episode psychosis are likely to cause further inequities in recovery and will require a response of health, education, employment, justice and political systems.